Upaya Pengawasan pada Metode Pelaksanaan Shotcrete dan Rockbolt pada Konstruksi Terowongan: Supervision Efforts on Shotcrete and Rockbolt Implementation Methods in Tunnel Construction - Noor, Rusandi; Saputra, Ferdy; Maulida, Istifalia; Zulkarnain, Isnaini; Pamungkas, Pulung Priyo (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The Samarinda Tunnel construction project is a strategic effort to support infrastructure development in East Kalimantan. This tunnel is located from Jalan Sultan Alimuddin, Sambutan District to Jalan Kakap, Samarinda Ilir District, with a length of 690 meters from the entrance (Inlet) to the exit (Outlet). This tunnel is expected to be able to reduce traffic jams that often occur on Jalan Otto Iskandar Dinata, Sungai Dama Village. This project is owned by the Samarinda City Government (PUPR) and is implemented by the contractor PT. PP Persero with PT. Ciria Jasa Cipta Mandiri is the supervising consultant. The construction method used is the New Austrian Tunneling Method (NATM), with a focus on the use of shotcrete and rockbolt to maintain the stability of the tunnel structure during and after the construction process. Shotcrete provides temporary protection against ground pressure, while rockbolt strengthens the rock mass around the tunnel. In this community service, observations were carried out using a participatory method, where observers were directly involved in the activities being observed. This approach allows for a deeper understanding of the application of shotcrete and rockbolts, as well as the effectiveness of the supervision carried out to ensure compliance with applicable technical specifications and standards.